Manipulations of black bear and coyote affect caribou calf survival. Issue 1 (30th September 2016) - Lewis, Keith P.; Gullage, Stephen E.; Fifield, David A.; Jennings, David H.; Mahoney, Shane P.
ABSTRACT: The population of woodland caribou ( Rangifer tarandus ) in Newfoundland declined from approximately 94, 000 to 32, 000 animals between 1996 and 2013. Poor calf survival was the primary cause of the population decline, largely because of predation of newborn calves by American black bear ( Ursus americanus ) and the non‐native coyote ( Canis latrans ). This situation offered an opportunity to test the efficacy of preventative management options such as diversionary feeding and lethal removal of predators for improving calf survival. We monitored caribou calves ( n = 536) in 4 calving areas (3 untreated, 1 treatment) for 2 years (2008–2009) followed by diversionary feeding of black bears and coyotes in 2010–2011 and lethal removal of coyotes in 2012–2013. We estimated calf survival for 70 days, the period calves and females remain on the calving grounds, and for 182 days, after which calves were considered recruited into the population. Calf survival was nearly constant over the 6‐year study period on the untreated areas. Calf survival was initially lower on the treatment area compared to the untreated areas but increased substantially on the treatment area during the lethal removal period, especially during the initial 70‐day period. Predation on calves by coyote decreased substantially during the lethal removal period. Diversionary feeding had little influence on survival rates. This study suggests that lethal removal of coyotes could be a viable management option for improving calf survival, but it is expensive and logistically challenging in remote field settings. © 2016 The Wildlife Society. Abstract : Diversionary feeding of black bears and coyotes did little to improve the survival of caribou calves in Newfoundland, but lethal removal of coyotes increased calf survival compared to untreated study areas. Removal of predators may be a viable management option if caribou populations continue to decline in Newfoundland.